Estudo do potencial migratório de células tumorais prostáticas expostas à fibronectina - Souza, Greyce Roberta de [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The prostate is a gland attached to the male genital system, found only in mammals, whose main function is to produce part of the seminal fluid. Prostatic lesions appear most commonly in middle-aged men and prostate cancer (PCa) is the most commonly cancer diagnosed and the second leading cause of cancer deaths among men in America and in Western European countries. The extracellular microenvironment is a complex network comprising extracellular matrix (ECM) and regulatory molecules. The ECM has a fundamental role in the regulation of many cellular events, such as adhesion, proliferation, differentiation, among others. A fine balance is maintained between the synthesis and degeneration of its components, and when unregulated can cause tissue damage and cancer. In the prostate, the interactions between the epithelial tissue and its stroma are responsible for maintaining normal physiological function through proliferative and migratory restrictions. When cancer develops, transformed cells lose these restrictions, while the stroma is adapted to support the function of the tumor. It is known that tumor cells with invasive potential acquire migratory phenotype associated with increased expression of genes involved in cell motility, allowing these cells to respond to signals from the tumor microenvironment. Thus, our study aimed to study the action of fibronectin, an ECM adhesion molecule, on migration of prostate cancer cells and the expression of molecules involved in this process. To achieve this goal, we performed the exposure of LNCaP and PC-3 cells to fibronectin in the concentration of 25 mg / mL and analyzed cell viability, morphology, total number of nucleoli, location and activity of matrix metalloproteinases -2 and -9 and the process of cell migration. Exposure to fibronectin did not alter cell viability and morphology, but increased the amount of nucleoli, as well as marking and the activity of MMP -2 and -9 and decreased migration...

A próstata é uma glândula anexa do sistema genital masculino, encontrada apenas em mamíferos, cuja principal função é produzir parte do fluido seminal. As lesões prostáticas surgem mais comumente em homens de meia idade e o câncer prostático (CaP) é o mais diagnosticado e a segunda causa de mortes por câncer entre os homens na América e nos países da Europa Ocidental. O microambiente extracelular trata-se de uma complexa rede que compreende a matriz extracelular (MEC) e moléculas reguladoras. A MEC possui papel fundamental na regulação de numerosos eventos celulares, tais como adesão, proliferação, diferenciação, entre outros. Um fino equilíbrio é mantido entre a síntese e degeneração de seus componentes, e quando desregulado pode causar dano tecidual e câncer. Na próstata, as interações entre o tecido epitelial e seu estroma são responsáveis em manter a função fisiológica normal, por meio de restrições proliferativas e migratórias. Quando o câncer se desenvolve, células transformadas perdem essas restrições, enquanto o estroma se adapta para sustentar a função do tumor. Sabe-se que as células tumorais com potencial invasivo adquirem fenótipo migratório associado ao aumento na expressão de genes envolvidos na motilidade celular, permitindo a essas células responder a sinais oriundos do microambiente tumoral. Assim, o nosso estudo teve como objetivo estudar a ação da fibronectina, uma molécula de adesão da MEC, sobre a migração de células tumorais prostáticas e a expressão de moléculas envolvidas nesse processo. Para isso, realizamos a exposição das células LNCaP e PC-3 à fibronectina na concentração de 25 μg/mL e analisamos viabilidade celular, morfologia, número total de nucléolos, atividade e localização das metaloproteinases de matriz -2 e -9 e o processo de migração celular. A exposição à fibronectina não alterou viabilidade celular e morfologia, mas aumentou...
Keywords: Próstata - Câncer; Matriz extracelular; Fibronectinas; Celulas - Cultura e meios de cultura; Prostate; Cancer